Pentingnya Pengalaman Kerja Dan Gender Terhadap Kualitas Kerja Karyawan - Mitasari Mitasari; Acep Samsudin; Nor Norisanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of work experience and gender on the quality of work of employees. This research uses descriptive method and associative method with quantitative approach. The population in this study are employees of the production division of PT. Star Comgistic Indonesia and the sample used were 280 respondets. The data analysys technique used is multiple linear regression analysis and the sample technique used is proportionate stratified random sampling. The result of this study indicate that simultaneously and partially the work experience and gender variables have a positive and significant effect on the quality of work of employees. The result of the f test are known from the fcount 168,672 > 3,028, indicating that the fcount value is greater than ftable and from the correlation result in this study, it has a strong and high value of 0,549. Meanwhile, from the results of the t test values, namely tcount 6,847 > 1,968, it shows than ttable so it can be concluded that work experience and gender have an influence on work quality. Keywords : Work Experience, Gender, Quality of Work